Twin picks: Disentangling the determinants of risk-taking in household portfolios - Laurent E. Calvet; Paolo Sodini (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
This paper investigates risk-taking in the liquid portfolios held by a large panel of Swedish twins. We document that the portfolio share invested in risky assets is an increasing and concave function of financial wealth, leading to different risk sensitivities across investors. Human capital, which we estimate directly from individual labor income, also drives risk-taking positively, while internal habit and expenditure commitments tend to reduce it. Our micro findings lend strong support to decreasing relative risk aversion and habit formation preferences. Furthermore, heterogeneous risk sensitivities across investors help reconcile individual preferences with representative-agent models.
urn:nbn:de:hebis:30:3-293833
Keywords: C23; D14; G11; 330; Asset allocation; communication; genetics; habit formation; human capital; labor income; leverage; participation; risk-taking; social interactions; twin study